PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT JALAN PADA RUMAH SAKIT DAERAH (RSUD) I.A MOIES DI SAMARINDA - -, Emi Liana (EKONOMIA, 2019)
I. A Moies hospital is a government hospital that has several problems in providing health services to patients, including some patients for speed in consolidating long waiting patients. And at least the completeness of the supply of medical equipment and some bad news about the I.A hospital. Moies.This study aims to find out: 1) Physical evidence (X1) has a significant effect on patient satisfaction, 2) reliability (X2) has a significant influence on patient satisfaction, 3) responsiveness (X3) has a significant positive influence for patient satisfaction , 4) (X4) has a positive influence on patient satisfaction, 5) empathy (X5) has a significant influence on patient satisfaction.The population in this study were all outpatients in the hospital (RSUD) I.A Moies in samarinda. The results concluded: 1) that H1 which was done correctly had a significant effect on patient satisfaction, 2) that H2 carried out had a significant effect on patient satisfaction, 3) that H3 was received had no significant effect on patient satisfaction, 4) that H4 was accepted as meaningless significant to patient satisfaction, 5) that H5 is willing to have no significant effect on patient satisfaction and H6 is spoken simultaneously with independent variables on patient satisfaction.